Penerapan Pengurangan Resiko Bencana Menuju Sekolah Aman Bencana di Madrasah Aliyah Negeri 1 Mataram - Syamsuddin Syamsuddin; Siti Alaa; Ridho Ahyana (Universitas Mathla'ul Anwar Banten, 2020)
IMPLEMENTATION OF DISASTER RISK REDUCTION TOWARDS A DISASTER SAFE SCHOOL AT MADRASAH ALIYAH NEGERI 1 MATARAM. Lombok is still in the recovery stage after the successive earthquake that occurred on the island in 2018. One of the most affected was the education sector, especially schools and students where many schools were damaged. The earthquake is not predictable so it can occur when the teaching and learning process is ongoing. To minimize casualties, socialization of disaster-safe schools is needed. The socialization of disaster safe schools has been carried out at Madrasah Aliyah Negeri 1 Mataram aimed at reducing disaster risk. The method of implementation is divided into lectures, dialogues and simulations. The material presented includes getting to know the BKRK School, Protap School Disaster Safe, knowing the Types of Disasters, knowing the Causes of Disasters, the Early Warning system in the event of a Disaster, Knowing First Aid and Evacuation, Knowing the Field Public Kitchen and Logistics. At the end of the activity a school disaster alert team was formed.